HIV-1 : molecular biology and pathogenesis : viral mechanisms : the first of a two-volume set - Jeang, Kuan-Teh (Advances in pharmacology (San Diego, Calif.), 2000)
The cumulative death toll from AIDS has reached 16.3 million individuals, and more than 33 million persons are currently living with HIV-1. Although it is one of the most-widely studied viruses, many mysteries remain about this pathogen. In this comprehensive two-volume set, HIV-1: Molecular Biology and Pathogenesis, leading investigators in HIV research present a timely picture of the molecular mechanisms which guide HIV-1 expression and replication and provide the most current clinical strategies for combating this virus. Twenty-six teams of experts unravel structure-function interactions of HIV-1 with host cells and the resulting pathological consequences, review strategies fo treatment, and describe ongoing progress in developing animal models and prophylactic vaccines. The two volumes, covering viral mechanisms and clinical applications, respectively, are written by an international collection of AIDS expers from North America, Europe, Australia, and Asia. Key Features. Detailed insights into viral packaging, expression, and assembly. Mechanistic understanding of how HIV interacts with receptors and infects cells. Delineation of virally encoded regulatory processes unique to HIV. Clinical Applications:. An updated review of current chemotherapeutics for HIV. New concepts in the discovery and design of novel anti-HIV drugs. The latest developments in HIV-vaccine research.